Preferences For Land As A Pawn Object In Notarial Deeds - Realizhar Adillah Kharisma Ramadhan (International Journal of Education, Vocational and Social Science, 2024)
Land plays a crucial role as collateral in loan or credit transactions in Indonesia. Although the term "land mortgage" is still commonly used, the legal provisions stipulate that land collateral must be carried out through a Deed of Mortgage (Akta Pemberian Hak Tanggungan - APHT). Registering Mortgage Rights is important as it provides preferential position for creditors in debt repayment, creates legal certainty, protects creditors' interests, enhances transparency, and supports investment security. However, there are still challenges related to errors committed by Notaries and Land Deed Officials (Pejabat Pembuat Akta Tanah - PPAT) which potentially violate legal provisions and ethical codes. Therefore, steps are needed to increase awareness of duty responsibilities and enforcement of ethical codes for Notaries and PPATs to maintain the integrity and public trust in the agrarian legal system.